2008
DOI: 10.1097/mop.0b013e3282f35f03
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of osteogenesis imperfecta: current concepts

Abstract: Recent medical and surgical advances have allowed improved safety, function and comfort in treating children with osteogenesis imperfecta. The selection of surgical techniques is dependent on surgeon experience, severity of disease and patient function, and availability of specific instrumentation. Intramedullary fixation rather than plating is preferred, and allowing early protected weight bearing and rehabilitation of children with ambulatory potential is the ideal goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 26 publications
0
103
0
8
Order By: Relevance
“…Wilkinson et al [20] reported that these new Sheffield rods result in less epiphyseal damage and has lower rates of complication. Later, it was reported that less joint damage, less invasive procedure, and lower mechanical complications are achieved with the Fassier-Duval nail developed by Fassier and Duval [21]. Besides, these nails have an advantage that removes knee arthrotomy in femoral surgery and ankle arthrotomy in tibial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Wilkinson et al [20] reported that these new Sheffield rods result in less epiphyseal damage and has lower rates of complication. Later, it was reported that less joint damage, less invasive procedure, and lower mechanical complications are achieved with the Fassier-Duval nail developed by Fassier and Duval [21]. Besides, these nails have an advantage that removes knee arthrotomy in femoral surgery and ankle arthrotomy in tibial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is no effective treatment for the patients with OI so far [27][28][29][30]. That is why, it seems to be of crucial importance to continue research studies investigating the role of new methods of therapy in patients with this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Это, не-сомненно, оказывает положительное влияние на функци-ональное состояние пациентов, связанное с увеличением их двигательной активности [8,9]. B. Boutaud и J.M.…”
Section: обсуждение основного результата исследованияunclassified